Normative values of incremental shuttle walk test in children and adolescents: an observational study - VISHNU VARDHAN,; TUSHAR PALEKAR,; PRIYANKA DHUKE,; GAURANG BAXI, (International Journal of Pharma and Bio Sciences, 2017)
Introduction - Cardiopulmonary exercise testing is the criterion standard for assessing exercise capacity. It is an important tool that provides complete assessment of the respiratory, cardiac and metabolic system. Objective - The purpose of this study was to find out the reference values for incremental shuttle walk test in children and adolescents and to correlate age, height, and weight and body mass index with incremental shuttle walk test. Method - 180 subjects were selected from the age group of 10 -16 years. The participants in this study were recruited from Schools in and around Pimpri. Weight and height was measured by calibrated weighing scale and stadiometer by standard anthropometric methods. Results - Data was checked for normality by using Shapiro- wilk test. Liner regression analysis using age, height, weight, and gender were applied with ISWT as a dependent variable. There was significant correlation with age (r= 0.430, p= 0.000), gender (p= 0.560), and there was no significant correlation with BMI (r= 0.041, p = 0.584). The variables included in the predicted equation were age, gender, body mass index. The predicted value for girls is 0 and for boys is 1.ISWT pred - 28.930+ (40.784*age)-(20.739*gender)-(3.479*BMI). Conclusion - The reference values were generated for 10 to 16 years of age group. The purpose of the study established a prediction equation for ISWTwhich can be used as a reference to evaluate exercise capacity for children and adolescents.